THE EFFECTS OF PROPOLIS HONEY CANDY CONSUMPTION ON MYELOPEROXIDASE ACTIVITY IN STIMULATED SALIVA - SAFINAZ, DARIN; SOEKANTO, SRI ANGKY; SARWONO, AGOENG TJAHJANI (International Journal of Applied Pharmaceutics, 2019)
Objective: Propolis is a natural product that contains flavonoids and has antibacterial effects that could decrease myeloperoxidase (MPO) activity in the saliva. Propolis honey candy is currently being developed and to analyze the effects of propolis honey candy on MPO activity in stimulated saliva. Methods: Stimulated saliva samples were collected from individuals who met the inclusion criteria before and after consumption of propolis honey candy twice a day for 7 days. Salivary samples were centrifuged to separate the supernatant and pellet. A 100-μl aliquot of the supernatant was directly added to the wells of a 96-well plate and mixed with 100 μl of substrate solution containing 3,3’-diaminobenzidine, guaiacol, dapsone, and Tris-HCl buffer. After incubation for 30 min at room temperature, MPO activity was measured by subtracting the absorbance value (wavelength of 450 nm) of the saliva samples from that of the blank control (distilled water). Results: The absorbance value of MPO activity of propolis honey candy was 0.071 before consumption and 0.076 after consumption. Conclusion: MPO activity significantly increased after the consumption of propolis honey candy (Wilcoxon signed-rank test, p<0.05).